Asymmetric Planetary Nebulae VII - Parker, Quentin A. (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This book contains the best and most up-to-date contributions in the field of late stage stellar evolution, as presented at the APNVII conference in Hong Kong in December 2017. A total of 60 scientists from 20 countries gathered to present, listen, interact and discuss the most current issues and problems in planetary nebulae and related objects research. The emphasis of this influential series of meetings, which was the seventh occasion over the last 20 years, has always been on the hypothesized and observed physical shaping mechanisms of the ejected nebulae that have such wonderful and intriguing forms. This special Galaxies conference issue of fully refereed contributions brings together a representative compilation of the meeting presentations in paper form. It captures the current "snap shot" status of this research field in some real sense. Such proceedings are well received and can be used as a reference material by both participants and all others working in the field for years to come.